The association of visceral adiposity index and diabetic kidney disease in elderly patients with type 2 diabetes mellitus: a cross-sectional study - Chen, Mengdie; Wang, Yiyun; Feng, Ping; Wu, Lijing; Lu, Chaoyin; Liang, Yao; Yang, Mengyao; Zheng, Qidong (Frontiers in Nutrition, 2025)
BackgroundResearch on the relationship between visceral adiposity index (VAI) and diabetic kidney disease (DKD) in elderly populations remains limited. This study aimed to investigate the potential link between the VAI and DKD in elderly patients with type 2 diabetes mellitus (T2DM).MethodsOverall, this cross-sectional analysis included 2,695 older individuals with T2DM from the National Metabolic Management Center (MMC) at Yuhuan Second People’s Hospital and Taizhou Central Hospital (Taizhou University Hospital) from September 2017 to May 2024. VAI was utilized as both a continuous and categorical variable with division into tertiles. Logistic regression and smooth curve fitting were employed, together with further stratified and interaction analyses.ResultsThis relationship was consistently observed across analyzed subgroups. The prevalence of DKD was significantly elevated in top tertile of VAI (T3) relative to the lowest (T1) (57.6% vs. 48.1%, p < 0.001). Following confounder adjustment, elevated VAI was linked with a higher risk of developing DKD. Each 1-unit rise in VAI (as a continuous variable) was related to a 4% greater risk of DKD (OR = 1.04, 95% CI: 1.01–1.08, p = 0.015). When VAI was categorized into tertiles, individuals in T3 showed a 1.29-fold greater risk of DKD compared with cases in T1 (OR = 1.29, 95% CI: 1.05–1.59, p = 0.015). A marked positive link was seen between VAI and DKD risk in all three regression models (P for trend < 0.001). Subgroup analyses revealed similar patterns, with a stronger association observed in participants with diabetes for ≥10 years relative to those with shorter disease (P for interaction = 0.036).ConclusionThis study highlights a positive VAI-DKD association in elderly T2DM patients, with higher VAI independently linked to an elevated risk of DKD, particularly in those with a longer history of diabetes. More prospective work is necessary to confirm these findings.